Age-related variation and multivariate analysis of internal and external egg quality traits in ISA Brown hens - Amireche, Douaa; Arzour-Lakehal, Nedjoua; Belagoune, Asma (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
This study evaluated age-related variations in internal and external egg quality traits in ISA Brown hens raised under semi-arid Algerian conditions. Hens were assessed at two production stages: 5,977 at peak lay (25–30 weeks) and 5,430 at late lay (75–80 weeks). A total of 360 eggs were collected (180 per stage), at a rate of 30 eggs per week, randomly selected at the beginning of each week. Egg weight, shell thickness, shape index, yolk and albumen indices, Haugh units, and yolk color were measured. A one-way analysis of variance (ANOVA) was used to detect age-related differences, Pearson correlation to examine interrelationships among traits, and principal component analysis (PCA) to identify general age-related patterns. Significant differences were observed between the two laying stages. Peak-lay eggs showed superior internal quality, particularly in albumen height and Haugh units, whereas late-lay eggs exhibited greater mass but reduced albumen integrity. Shell thickness and yolk shape remained relatively stable. Correlation analysis revealed stronger trait associations during peak lay, which weakened with advancing age. PCA showed contrasting age-related trends between egg size and internal quality: egg size increased with age, whereas internal quality declined, while shell- and yolk-related traits remained relatively constant. The findings of this study apply to hens up to 80 weeks of age. Further studies covering longer production cycles are recommended to determine whether these patterns persist beyond this period.